Implementation of Women's Representation as Members of the General Election Commission Based on Law No. 7 of 2017 on General Elections. - Sukardin; Suartini; Anas Lutfi (Jurnal Hukum Volkgeist, 2023)
The topic of women's quotas can be a good entry point to explore what limits and enhances substantive representation of women. Additionally, women's quotas are closely related to the debate on descriptive and substantive representation when associating quota policies, representation, and the effects of these quota policies. Women's representation in election organizers is crucial to ensure fair, equitable, and inclusive elections. Moreover, this is related to the issue of affirmative action. Affirmative action is a policy that provides special treatment to disadvantaged or marginalized groups, such as women, in order to enhance their representation in election organizers. This policy can take the form of quotas, reservations, or other affirmative programs. This research aims to analyze the Implementation and Factors affecting the fulfillment of the 30% Women's Representation quota in General Elections organizers in Indonesia based on Law No. 7 of 2017 regarding General Elections Research.